A retrospective study on the efficacy of the ERAS protocol in patients who underwent laparoscopic left and right colectomy surgeries - Zhao, Xuemei; Jin, Siyu; Peng, Mingxiu; Wang, Jingjing (Frontiers in Surgery, 2024)
Objective: Retrospective analysis and comparison of the effects of Enhanced Recovery After Surgery (ERAS) protocol for patients having left and right colectomy surgeries.Out of the patients admitted to Chengdu Shang Jin Nan Fu Hospital and West China Hospital from December 2019 to December 2022, a total of 498 who met the inclusion criteria were selected, 255 with right colectomy(RC) and 243 with left colectomy(LC). Under the conditions of strict compliance with ERAS protocol, the relevant physical indexes of RC and LC, including postoperative rehabilitation(especially median post-operative stay) and complications(especially prolonged postoperative ileus, PPOI), were statistically analyzed and compared.In terms of intraoperative variables, fluid doses were higher in the LC group than in the RC group (P<0.05), and there was no significant difference between them in terms of operative time, blood loss, need for open surgery, peritoneal contamination, epidural catheter placement, or opioid use (P>0.05). Compared with the RC group, the LC group had a higher intake of oral liquid at the second postoperative day(POD), and faster first flatulence (P<0.05). 30 (11.76%) RC patients required nasogastric tube insertion, while only 3 (1.23%) patients in the LC group required the same (P <0.05). Prolonged postoperative ileus (PPOI) occurred in 48 (18.82%) and 29 (11.93%) patients in the RC and LC groups, respectively (P<0.05). No significant differences in terms of postoperative complications or length of hospital stay (LoS). stay were observed.As the location of colon cancer changes, the effectiveness of ERAS also varies. More personalized and precise ERAS protocols can reduce the incidence of postoperative complications and promote rapid recovery after surgery.